Mechanistic Kinetic Analysis of Fast Pyrolysis of Vanillin to Primary Phenols - Yerrayya, Attada; Natarajan, Upendra; Vinu, Ravikrishnan (Frontiers in Energy Research, 2022)
Vanillin is a major fine chemical in the flavoring industry and one of the pyrolysates from lignin. In order to understand the primary decomposition pathways of vanillin, analytical fast pyrolysis experiments were performed in the temperature range of 500°C–650°C, and the primary pyrolysates were quantified. The proposed pyrolysis chemistry involves 31 elementary reactions of 23 species. Thermodynamic and kinetic analyses were performed using quantum chemical density functional theory calculations. Reaction pathways for the formation of three major phenolics, viz., guaiacol, 5-formylsalicyaldehyde and 4-hydroxybenzaldehyde, that accounted for ∼80 wt% yield at 650°C, were proposed. Based on the bond dissociation energies (BDEs) of homolytic cleavage of the various bonds in vanillin, the primary reaction is shown to involve the cleavage of O–CH3 bond whose BDE is 61.4 kcal mol−1. New bimolecular reactions such as ipso-addition involving the reaction of vanillin with hydrogen and methyl radicals were proposed. The generation of 4-hydroxy methoxybenzyl radical was found to be vital for the formation of guaiacol, while 4-hydroxy-3-(λ3-methoxyl) benzaldehyde radical was the key intermediate for the formation of 5-formylsalicyaldehyde. Multiple pathways for the formation of guaiacol, 5-formylsalicyaldehyde, catechol and 4-hydroxybenzaldehyde were evaluated. In order to track the time evolution of vanillin and its major pyrolysates, a detailed kinetic model was developed using the elementary reactions and their Arrhenius rate parameters. Based on the kinetic model, it is inferred that the timescale of fast pyrolysis is captured well by the model.